Compliance Level of PAUD Students in Brushing with the Interactive Calendar Guide - Laela, Dewi Sodja; Aliyah, Raisya; Restuning, Sekar; Fatikhah, Nurul (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Brushing teeth properly and correctly must be instilled in children from an early age so that they become accustomed to living a clean and healthy lifestyle. Dental health education can help people develop good brushing habits. Brushing your teeth in the morning and evening for 21 days is an interactive calendar designed to control the implementation of brushing your teeth in the morning and evening. The objective of this study was to assess PAUD (Pre-School) students' compliance with morning and night toothbrushing using an interactive calendar guide to brushing their teeth in the morning and evening for 21 days. The research method used is pre-experimental. Simple random sampling method was also administered. The research intervention was conducted on 32 PAUD Bahagia Sukapura and Al Abror students. A questionnaire and an interactive calendar sheet were used as research instruments. The results showed that before the intervention, the average score of PAUD children's compliance with brushing their teeth in the morning and evening was 46.9063, but after the intervention, it increased to 79.0313. Before the intervention, the level of adherence to brushing teeth in the morning and evening was in the less compliant category (40.6%), but after the intervention with an interactive calendar, it increased to (96.9%). The Wilcoxon Sign Rank Test analysis revealed a difference in pre- and post-intervention scores on children's compliance data in brushing their teeth using the morning and evening brushing calendar for 21 days, with a p-value (0.000) <0.05. Brushing their teeth twice a day in the morning and evening for 21 days is effective in increasing PAUD children's adherence to brushing their teeth twice a day in the morning and evening.